Pengaruh return on equity (roe), cash ratio (cr), debt to equity ratio (der) dan earning per share (eps) terhadap dividen payout ratio pada perusahaan jakarta islamic index yang listing di bei Periode 2008-2012 Oleh: - Junaidi '; Azwir Nasir; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of the return on equity (ROE) , cash ratio (CR) , debt-to- equity ratio (DER) and earnings per share (EPS ) affect the dividend payout ratio simultaneously and partially to the company's dividend payout ratio (DPR) in jakarta islamic index IDX listings in the period 2008-2012 . The sample in this study is a company Jakarta Islamic Index are listed on the Stock Exchange from 2008 - 2012 sebanyak 23 companies .The analytical method used is regression analysis.Priod to the statistical t-test againts multiple rergression equation, the test is done first classical assumption of normality of the data, autocorrelation, multicollinearity and heteroscedasticityThe results of this study stated partially ROE significantly affect Parliament variable with a P value 0.029 . While the cash ratio ( CR ) , debt-to- equity ratio ( DER ) and earnings per share ( EPS ) does not affect the dividend payout ratio .Adjusted R Square shows the value of 0.024 . This indicates that 2.4 % of DPR influenced by determinant variables in the model while the rest is explained by other variables not included in the model , it is necessary to add other variables that influence the House so as to have maximum results and adequate .Keywords : Return On Equity (ROE), Cash Ratio (CR), Debt To Equity Ratio (DER) Dan Earning Per Share (EPS) Terhadap Dividend Payout Ratio (DPR)